Perancangan Aplikasi Pengujian Produk Berbasis Web; Studi Kasus pada Program Studi Program Profesi Insinyur dari Unsur Tenaga Pendidik Universitas Sriwijaya - Nugrasyah, Amrillah; Berniko , Muhammad Aldy; Mohruni, Amrifan Saladin (Jurnal Rekayasa Mesin, 2024)
Quality Assurance is a term that refers to an evaluation process that includes monitoring and guaranteeing the quality of something, one of which is Recognition of Past Learning (RPL). In this case, RPL is one of the educational pathways at Sriwijaya University in the Engineer Professional Study Program (PSSPI). This study aims to produce a product testing application for RPL student assessment that is not yet available. There are several tools and software used to design this application, such as Microsoft Visual Studio Code, MySQL, PHP, CSS, HTML, REST API, XAMPP, and also Laravel. This application is designed using the Waterfall method, meaning the next design process cannot be carried out if the previous design process has not been completed. There are 5 stages in this waterfall method, namely requirements definition, system and software design, implementation and unit testing, integration, and system testing, and operation and maintenance.